Penerapan Model Pembelajaran Role Playing Untuk Meningkatkan Motivasi Ekstrinsik Belajar PAI dan BP Siswa - Dirja, Muldani Surya; Muliati, Indah (Prodi Pendidikan Keagamaan Islam, 2025)
This research is motivated by the problem of lack of enthusiasm and motivation for students to learn, so a learning model is needed that can improve this. This study aims to determine the application of the role playing learning model in increasing the extrinsic motivation of PAI and BP students in grade V at SDIT Buah Hati Air Tawar Barat Padang. This study uses a qualitative method with a case study approach. Overall, the results of the analysis show: there are several steps to implement it, namely: teachers provide stimulus and explanations to students; teachers provide learning motivation to students; the teacher provides the script of the scenario in the form of a dialogue conversation to all students; the teacher frees students to choose their group mates; teachers ask students to discuss with each other, help and work together; Each group of students is required to role-play until the last group; the teacher discusses with students regarding the results of role-playing in each group and students' understanding of the story being acted out; the teacher conveys general conclusions and evaluations of learning outcomes; The teacher closed the learning and gave assignments to the students.